A METHOD OF SELECTIVE PROCESSING OF VIDEO SEGMENTS TO IMPROVE THE QUALITY OF VIDEO IMAGES IN INTELLIGENT ANALYSIS SYSTEMS - Barannik, Vladimir; Ustymenko, Fydor; Barannik, Valerii; Miltcin, Ihor; Yudin, Oleksandr (Science-based technologies, 2025)
The world is currently experiencing the fourth industrial revolution, marked by the emergence and development of production automation technologies. One of the technology groups that is increasingly being utilized in various industrial and service sectors is intelligent image processing technologies. However, tools developed using these technologies have a number of limitations that restrict their effectiveness. One such limitation is the existing dependence of the performance of intelligent image processing systems on the quality of the input images. It has been demonstrated that the advancement of modern technologies for processing and compressing video images imposes new requirements on the quality of the images received by intelligent information processing systems. This study investigates the features of selective video segment processing aimed at enhancing their informativeness and adaptation to intelligent technologies. It has been concluded that traditional processing methods, such as noise filtering or artifact removal, do not address the problem of image quality loss during the initial compression stages. A novel approach has been proposed, based on analyzing the intensity and range of color changes in image segments. To achieve this goal, a combination of statistical methods, spectral analysis, and computer modeling was employed. An innovative method for selectively identifying significant segments has been developed, relying on their informational and semantic load. The study presents a metric for evaluating segment informativeness, which enables effective classification of segments into informative, mixed, and non-informative blocks. This approach improves the quality of critical image areas, reduces noise impact, and ensures processing adaptability to the specificity of input data. The selective processing methodology enhances the efficiency of intelligent systems by preserving the quality of significant regions during compression and adapting to specific processing requirements. The results of this work can be applied in video surveillance systems, autonomous transportation, medical diagnostics, and other fields where image quality is of critical importance.